Computer Aided Learning (CAL) For Malaysian O'Level Mathematics Curriculum (CALMOMC) - Norshuhada, Shiratuddin (1995)
This project is about a CAL system on Malaysian O’Level Mathematics Curriculum (CALMOMC). The first chapter simply discusses the era of electronic classroom in Malaysia. The second chapter then, reports about the Malaysian Mathematics Curriculum, its objectives and the Education Philosophy. The third chapter covers the importance and benefits of CAL. There is also a discussion on traditional teaching methods and CAL VS the traditional methods. The report then discusses the Author-ware package in details. Why Authorware is chosen, steps to produce a program, Author-ware VS Other CAL Oriented Languages and the characteristics of a CAL language are also covered. There is also a chapter that views the proposed system in general. This chapter contains the system structure, system flowcharts, user manual and system screens. In order to measure the success of the system, an evaluation was carried out. The results of the evaluation are discussed in chapter six. Lastly, conclusion and suggestions for future improvements are in chapter seven.